On modeling building evacuation route plans by resorting to P-graph - García Ojeda, Juan C. (Revista Colombiana de Computación, 2011)
This paper presents basic ideas on the application of the P-graph framework for modeling building evacuation routes and computing the optimal one. To do so, P-graph relies on both combinatorial and graph techniques for facilitating such a work.